Modern Electronic Educational Technologies in the Process of E-Learning - Kovalenko, Oksana; Hontarenko, Iryna (Educational Challenges, 2023)
The purpose of the study is to focus attention on the positive aspects of using E-learning in contrast to the traditional format in a modern university, as well as on the need for effective management of E-learning in order to improve the quality of education. Methodology. The following research methods were used to solve the assigned tasks: theoretical – analysis of scientific sources, pedagogical and teaching-methodical materials, comparison; empirical – generalization of pedagogical experience; a pedagogical experiment to check the effectiveness of organizing students' work using LMS Moodle platform. Results. This study focuses on the positive aspects of using E-learning. Introducing E-learning into the educational process provides new opportunities, provides everyone with the necessary knowledge and develops digital literacy skills. The study analyses the current state of е-learning in higher education and summarizes some theoretical issues of using LMS Moodle, both positive and negative. It offers practical suggestions for the qualitative integration of E-learning into the teaching and learning process based on practical and good management of the E-learning process. The case of Simon Kuznets Kharkiv National University of Economics is used, which implemented the distance learning platform, a platform called “Personal Learning Systems” (PLS). A management system for electronic learning at the university was developed based on the modelling method, the primary purpose of which is to use modern electronic educational technologies in the educational process, to prepare a methodological base for electronic educational resources, and to improve electronic educational technologies in the format of electronic learning. Conclusions. The E-learning management system “personal learning systems” (PLS) in the university is considered an information-management system whose primary purpose is the application of modern electronic educational technologies in the educational process, in the preparation of a methodological base of electronic educational resources, improvement of electronic educational technologies in a distance learning format.